A criação teatral a partir do conto o gato preto de Edgar Allan Poe: processos cênicos com o Grupo de Teatro Mímesis do IFMA/Campus Grajaú. - GUIMARÃES, Rafaela Maria França (2020)
This research intends to investigate the creative process of the students who participate in the Theater Group Mímesis at IFMA/ Grajaú Campus using as starting point the narrative genre short story through the work “The Black Cat”, by Edgar Allan Poe and its passage to the theatrical language. It is a qualitative approach, a participatory action research and a descriptive research, in which a path has been drawn by using the following creative methods: study of the short story; thoretical research; grupal reading; logbooks; storytelling with exterior resources; narrative recording; construction of drama fragments; brainstorming in posters; slam; scene montage; exercises with/about narrator and narratives; theater games; study of character with experimentation of characterization/ make up and work with shadow projection. Theses methods were used in the attempt of uderstanding ways to the scenic creation through the short story genre, which results pointed to the construction of the narrative solos “Faces de Hamlet”, staging by using the animation language and also the theater transcription “The Black Cat”. This proposal brings experiences that instigate the reflection about the importance of the scenic creation process in the artistic production at school.